A Study Depicting Histomorphology of Third Trimester Placenta in SARS-Cov-2 Positive Women - Jain, Neelanjali; Malik, Reeni; Balani, Sharda (Annals of Pathology and Laboratory Medicine, 2021)
Background: This study aims to detect association of SARS-COV-2 infection in terms of histopathological changes in the third trimester placenta. Methods: SARS COV 2 positive placenta cases received in Department of Pathology, Gandhi Medical College and Hamidia Hospital, Bhopal, Madhya Pradesh. 7 cases were sent for histopathological examination. Clinical details, history, details of relevant investigation like D-dimer, blood reports etc. was taken from the electronic medical records and requisition form received in the Department of Pathology. Histopathological findings were analyzed and recorded. Result: This is a case series depicting various histopathological changes in term placenta of 7 SARS Corona Virus 2 (COV-2) positive women in the age group of 20 years to 35 years exhibiting symptoms ranging from mild to severe degree. The major histopathological finding noticed is under perfusion of placenta of maternal side in greater extent as compared to fetal side under perfusion followed by signs of inflammation of membranes viz chorionitis and chorioamnionitis. Hence, through the study, we want to highlight micro vasculopathy as one of the pathophysiological features of SARS Corona Virus 2 (COV-2) which might be leading to these histopathological findings and its correlation with elevated levels of D – Dimer. Conclusion: Covid 19 positive women with third trimester of placenta do not express any specific histomorphological findings. Our study shows only signs of maternal and fetal vascular under perfusion with mild acute chorionitis which might have a relationship to a microvascular disease induced by SARS COVID 19 virus, yet this cannot be ruled out consistently proven several associated factors.